Broadcast Media and Climate Change Awareness in Nigeria: A Study of Residents’ Perception in Edo State - David, Temitope Sarah; Obaje, Comfort E.; Ezegwu, Daniel Toochukwu (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This paper explores the perceptions of people in the Edo State about the report about climate change in Nigeria on the broadcast media. It is based on the Agenda-Setting and Perception Theories in that it explores the level of media exposure, relevance of the content and the subsequent change of attitude. The issue that inspired the research is that there is always a disparity between the high aggregate knowledge of climate change and the little exposure to climate content via Nigerian broadcast media. To fill this gap, the following research questions were formulated: How often do the residents of Edo state receive the information about climate change on broadcast media? What are the most reported problems? What is the effect of exposure to media on the minds of people? The research design was a survey research design by the use of a structured questionnaire that was given to 384 respondents in the three senatorial districts of Edo state out of which 372 respondents were retrieved and analyzed using descriptive statistics. The results indicate that general awareness of climate change is high but the real exposure towards broadcast media reportage is low. The most listened to platform was Radio, especially the Independent Radio and Edo Broadcasting Service. The most numerous issue that was reported was flooding whereas complex issues such as emissions and policy coverage gained minimal coverage. Media messages had a positive effect on the attitude of people who were reached despite the low exposure. It is concluded that the potential of broadcast media in Edo State have not been fully used in climate communication and suggestions will be to enhance better training of journalists, strategic environmental programs, and diversified broadcast messages to enhance the level of understanding and interest of the people on the issues of climate.